From chemical mutagenesis to post-expression mutagenesis: A 50 year odyssey. - Wright, T; Vallée, M; Davis, B (Wiley, 2016)
Site-directed (gene) mutagenesis has been the most useful method available for the conversion of one amino acid residue of a given protein into another. Until relatively recently, this strategy was limited to the twenty standard amino acids. The ongoing maturation of stop codon suppression and related technologies for unnatural amino acid incorporation has greatly expanded access to nonstandard amino acids by expanding the scope of the translational apparatus. However, the necessity for translation of genetic changes restricts the diversity of residues that may be incorporated. Herein we highlight an alternative approach, termed post-expression mutagenesis, which operates at the level of the very functional biomolecules themselves. Using the lens of retrosynthesis, we highlight prospects for new strategies in protein modification, alteration, and construction which will enable protein science to move beyond the constraints of the “translational filter” and lead to a true synthetic biology.